Risk management : lever for SME development and stakeholder value creation - Bérard, Céline; Teyssier, Christine (ISTE ; Wiley-ISTE, 2017)
Risk management practices are growing both in number and complexity in businesses, notably driven by new regulatory standards that feature risk management at their core. Although large businesses are more likely to adopt a formal, holistic approach to risk management, the stakes are just as high for SMEs.